A Comparative Environmental Life Cycle Assessment of the Combustion of Ammonia/Methane Fuels in a Tangential Swirl Burner - Razon, Luis F.; Valera-Medina, Agustin (Frontiers in Chemical Engineering, 2021)
Ammonia has been proposed as a replacement for fossil fuels. Like hydrogen, emissions from the combustion of ammonia are carbon-free. Unlike hydrogen, ammonia is more energy dense, less explosive, and there exists extensive experience in its distribution. However, ammonia has a low flame speed and combustion emits nitrogen oxides. Ammonia is produced via the Haber-Bosch process which consumes large amounts of fossil fuels and requires high temperatures and pressures. A life cycle assessment to determine potential environmental advantages and disadvantages of using ammonia is necessary. In this work, emissions data from experiments with generating heat from tangential swirl burners using ammonia cofired with methane employing currently available technologies were utilized to estimate the environmental impacts that may be expected. Seven ammonia sources were combined with two methane sources to create 14 scenarios. The impacts from these 14 scenarios were compared to those expected from using pure methane. The results show that using ammonia from present-day commercial production methods will result in worse global warming potentials than using methane to generate the same amount of heat. Only two scenarios, methane from biogas combined with ammonia from hydrogen from electricity and nuclear power via electrolysis and subsequent ammonia synthesis using nitrogen from the air, showed reductions in global warming potential. Subsequent analysis of other environmental impacts for these two scenarios showed potentially lower impacts for respiratory organics, terrestrial acidification-nutrification and aquatic acidification depending on how the burner is operated. The other 8 environmental impacts were worse than the methane scenario because of activities intrinsic to the generation of electricity via wind power and nuclear fission. The results show that generating heat from a tangential swirl burner using ammonia currently available technologies will not necessarily result in improved environmental benefits in all categories. Improvements in renewable energy technologies could change these results positively. Other means of producing ammonia and improved means of converting ammonia to energy must continue to be explored.